Biostimulation through natural biological inputs on fruiting, nutrient availability and rhizosphere microbiome in legume intercropped ‘Sweet Charlie’ strawberry (Fragaria × Ananassa Duch.) - Pramod Kumar; Rajeshwar Singh Chandel; Subhash Chander Verma; Nisha Sharma; Simran Saini; Rohit Bishist; Suman Lata (BMC Plant Biology)
Abstract Conventional agricultural practices have been associated with detrimental effects such as soil degradation, reduction in biodiversity, environmental contamination due to agrochemical use, and a decrease in the nutritional quality of crops. These challenges necessitate a transition toward sustainable and ecologically sound farming systems. Natural Farming, the regenerative agriculture has shown promising results in restoring soil organic carbon, enhancing microbial biomass and enzymatic activity, improving water retention, and supporting nutrient cycling through natural inputs. This approach emphasizes on-farm biomass recycling while excluding all synthetic inputs, fostering an economic and environment-friendly system. The current study was carried out over two cropping seasons to explore the potential of natural farm inputs on sustainable and high-quality strawberry crop production. Biological modifications namely, Ghan-jeevamrit and Jeevamrit have been used. Ghan-jeevamrit contained 4–5 days air dried indigenous cow dung (100 kg), raw sugar (1 kg), phosphorus solubilizing bacteria rich pulse flour (1 kg), cow urine (3 L) and forest soil (250 g). Liquid microbial culture of Jeevamrit contained cow dung-urine (pH-5.65, EC-0.23 dS/m) and was enriched with Azotobacter chroococcum, Pseudomonas species and actinobacteria. The trial included, Ghan-jeevamrit-2.5 kg/m2; Ghan-jeevamrit-5 kg/m2; Ghan-jeevamrit-2.5 kg/m2 + Jeevamrit-2.0 L/m2; Jeevamrit-2.0 L/m2; Ghan-jeevamrit-2.5 kg/m2 + Jeevamrit-1.0 L/m2 and Farmyard manure (FYM)-100% of nitrogen equivalent basis. The results showed that Ghan-jeevamrit-2.5 kg/m2 + Jeevamrit-2.0 L/m2 significantly improved the production parameters, quality metrics and yield of strawberries. Microbial formulations resulted in maximum build-up of bacteria, fungi and arbuscular-mycorrhizal fungi (AMF) in the soils which received Ghan-jeevamrit-2.5 kg/m2 + Jeevamrit-2.0 L/m2. Bio-mobilization and recycling of native nutrients through combined application of Ghan-jeevamrit and Jeevamrit encouraged dehydrogenases and acid phosphatase enzymatic activity to maintain soil health and productivity for long-term and sustainable strawberry production. Principal component analysis (PCA) revealed highest cumulative variation for AMF population, dehydrogenase, soil bacteria and fungi. The study further recognised as a practical and affordable solution to farmers in order to improve soil health, increase crop nutrition and lower production costs. This study highlights that the adoption of natural farm inputs can enhance soil biological health, while, promoting high-quality and sustainable strawberry production.